Regulating Dynamic Electrochemical Interface of LiNi0.5Mn1.5O4 Spinel Cathode for Realizing Simultaneous Mn and Ni Redox in Rechargeable Lithium Batteries - Lim, Gukhyun; Shin, Dongki; Chae, Keun Hwa; Cho, Min Kyung; Kim, Chan; Sohn, Seok Su; Lee, Minah; Hong, Jihyun (Wiley-VCH Verlag, 2022)
The exploding electric-vehicle market requires cost-effective high-energy materials for rechargeable lithium batteries. The manganese-rich spinel oxide LiNi0.5Mn1.5O4 (LNMO) can store a capacity greater than 200 mAh g(-1) based on the multi-cation (Ni2+/Ni4+ and Mn3+/Mn4+) redox centers. However, its practical capacity is limited to Ni2+/Ni4+ redox (135 mAh g(-1)) due to the poor reversibility of Mn3+/Mn4+ redox. This instability is generally attributed to the Jahn-Teller distortion of Mn3+ and its disproportionation, which leads to severe Mn dissolution. Herein, for the first time, the excellent reversibility of Mn3+/Mn4+ redox within 2.3-4.3 V is demonstrated, requiring revisiting the previous theory. LNMO loses capacity only within a wide voltage range of 2.3-4.9 V. It is revealed that a dynamic evolution of the electrochemical interface, for example, potential-driven rocksalt phase formation and decomposition, repeatedly occurs during cycling. The interfacial evolution induces electrolyte degradation and surface passivation, impeding the charge-transfer reactions. It is further demonstrated that stabilizing the interface by electrolyte modification extends the cycle life of LNMO while using the multi-cation redox, enabling 71.5% capacity retention of LNMO after 500 cycles. The unveiled dynamic oxide interface will propose a new guideline for developing Mn-rich cathodes by realizing the reversible Mn redox.